The Effects of Using Adapted Science eBooks Within Shared Reading on Comprehension and Task Engagement of Students with Autism Spectrum Disorder. - Kim, So Yeon; Rispoli, Mandy; Mason, Rose A.; Lory, Catharine; Gregori, Emily; Roberts, Carly A.; Whitford, Denise; Wang, Danni (Journal of Autism & Developmental Disorders, 2025)
The purpose of this study was to examine the effects of using adapted science eBooks within shared reading on comprehension and task engagement of high school students with autism spectrum disorder (ASD). A grade-level science textbook was selected and converted into an eBook format, incorporating various visual and auditory features (e.g., text-to-speech, summarized sentences, highlighted keywords) and presented on an iPad. The shared reading intervention included before, during, and after reading strategies (i.e., pre-teaching target vocabulary words, sharing information, retelling), with direct instruction on locating literal information. The intervention effects on reading comprehension and task engagement were evaluated using a single-case multiple probe design. The results of this study indicated that all participants demonstrated improvements in reading comprehension. Despite the longer intervention sessions compared to the baseline, all participants exhibited similar or enhanced levels of task engagement during the intervention sessions. The findings of this study provide empirical evidence supporting the use of adapted eBooks within shared reading as a means to increase access to grade-level science texts for high school students with ASD while maintaining a high level of task engagement. This intervention holds promise for improving the learning outcomes for students with ASD in science content area.